Construction of Ultrathin Nitrogen-Doped Porous Carbon Nanospheres Coated With Polyaniline Nanorods for Asymmetric Supercapacitors - Yu, Pingping; Wang, Qunliang; Zheng, Lingxia; Jiang, Yanfeng (Frontiers in Chemistry, 2019)
Porous carbon materials produced by biomass have been widely studied for high performance supercapacitor due to their abundance, low price, and renewable. In this paper, the series of nitrogen-doped hierarchical porous carbon nanospheres (HPCN)/polyaniline (HPCN/PANI) nanocomposites is reported, which is prepared via in-situ polymerization. A novel approach with one-step pyrolysis of wheat flour mixed with urea and ZnCl2 is proposed to prepare the HPCN with surface area of 930 m2/g. Ultrathin HPCN pyrolysised at 900°C (~3 nm in thickness) electrode displays a gravimetric capacitance of 168 F/g and remarkable cyclability with losing 5% of the maximum capacitance after 5,000 cycles. The interconnected porous texture permits depositing of well-ordered polyaniline nanorods and allows a fast absorption/desorption of electrolyte. HPCN/PANI with short diffusion pathway possesses high gravimetric capacitance of 783 F/g. It can qualify HPCN/PANI to be used as cathode in assembling asymmetric supercapacitor with HPCN as anode, and which displays an exceptional specific capacitance of 81.2 F/g. Moreover, HPCN/PANI//HPCN device presents excellent cyclability with 88.4% retention of initial capacity over 10,000 cycles. This work will provide a simple and economical protocol to prepare the sustainable biomass materials based electrodes for energy storage applications.